Pengaruh Media Latihan Beban Botol Berisi Pasir Terhadap Kemampuan Servis Atas Bola Voli - Kaitam, Lateng; Anwar, Saiful; Pratama, Leo (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The purpose of this research is to find out how the influence of sand-filled bottle weight training media has on the volleyball service ability of class X students at SMK Negeri 3 Sorong City. The type of research used is experimental research. The results of this initial test were an average of 50 percent with an increase in the final test results of service strokes above an average of 80-90 percent with the predicate points